Copper(ii) complexes of N-propargyl cyclam ligands reveal a range of coordination modes and colours, and unexpected reactivity. Issue 11 (26th February 2021) - Counsell, Andrew J.; Yu, Mingfeng; Shi, Mengying; Jones, Angus T.; Batten, James M.; Turner, Peter; Todd, Matthew H.; Rutledge, Peter J.
Abstract : Copper(ii ) complexes of cyclam ligands with 1, 2, 3 or 4 pendant alkynes have been prepared and characterised crystallographically and spectroscopically. An unexpected hydroalkoxylation reaction is observed, affording an enol ether from the alkyne. Abstract : The coordination chemistry of N -functionalised cyclam ligands has a rich history, yet cyclam derivatives with pendant alkynes are largely unexplored. This is despite the significant potential and burgeoning application of N -propargyl cyclams and related compounds in the creation of diversely functionalised cyclam derivatives via copper-catalysed azide–alkyne 'click' reactions. Herein we describe single crystal X-ray diffraction and spectroscopic investigations of the coordination chemistry of copper(ii ) complexes of cyclam derivatives with between 1 and 4 pendant alkynes. The crystal structures of these copper complexes unexpectedly reveal a range of coordination modes, and the surprising occurrence of five unique complexes within a single recrystallisation of the tetra- N -propargyl cyclam ligand. One of these species exhibits weak intramolecular copper-alkyne coordination, and another is formed by a surprising intramolecular copper-mediated hydroalkoxylation reaction with the solvent methanol, transforming one of the pendant alkynes to an enol ether. Multiple functionalisation of the tetra- N -propargyl ligand is demonstrated via a 'tetra-click' reaction with benzyl azide, and the copper-binding behaviour of the resulting tetra-triazole ligand is characterised spectroscopically.